(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2010)
Whilst human aggression is discussed widely in psychological literature, it is often discussed as if it is outside the control of the somewhat passive individual, who requires interventions to prevent or control it, implying that all aggression is pathological. Whilst this has its uses, it provides only a one-sided view, and contributes little to a fuller understanding of the experience of aggression. In order to begin to redress this, this paper presents findings from an Interpretative Phenomenological Analysis (IPA) into therapeutic practitioners’ experience of aggression. Their accounts attended to the bodily sensations, feelings and impulses that the experience of aggression, both their own and other people’s, engendered. The tendency to want to ’rid’ aggression was associated with fear, anger, and an impulse to ’attack back’. Participants suggested the need to engage with these emotions, resisting the impulse to ’attack back’, in order to be able to allow clients to bring their aggression, explore it, and engage with it in a constructive manner. In contrast to the current psychological literature, participants described themselves and their work as active in engendering aggression, and outlined the normality of it. This raises questions for clients and clinicians in the need to acknowledge the impact on the therapeutic relationship itself and raises wider socio-political questions about the current policy on aggression within our society.